Mouse Cochlear Whole Mount Immunofluorescence - Akil, Omar (Bio Protoc, 2013)
This protocol comprises the entire process of immunofluorescence staining on mouse cochlea whole mount, starting from tissue preparation to the mounting of the tissue. This technique provides “three-dimensional” views of the stained components in order to determine the localization of a protein of interest in the tissue in its natural state and environment.